Advanced lung cancer inflammation index as a diagnostic indicator of bone turnover in osteoporotic fracture patients: a non-linear analysis - Wang, Jiahao; Zhu, Mengcheng; Wang, Weihong; Li, Chong; Lu, Ke; Hao, Yanming (Frontiers in Endocrinology, 2026)
BackgroundOsteoporotic fractures (OPFs) are a major health concern in older adults and are strongly influenced by systemic inflammation and nutritional status. The Advanced Lung Cancer Inflammation Index (ALI), which combines body mass index, serum albumin, and neutrophil–lymphocyte ratio, has been linked to outcomes in chronic diseases, but its relationship with bone turnover markers (BTMs) in OPF remains unclear.MethodsWe analyzed 826 Chinese patients with OPFs admitted from 2017 to 2024. Bone formation and resorption were assessed using serum procollagen type I N-terminal propeptide (P1NP) and β-isomerized C-terminal telopeptide of type I collagen (β-CTX). ALI was log-transformed (lnALI) for analysis. Multivariable linear, generalized additive, and piecewise regression models were applied, adjusting for demographic, clinical, biochemical, and perioperative factors.ResultsA higher ALI was independently and positively associated with P1NP (β = 9.33, 95% confidence interval [CI]: 5.82–12.84, p < 0.001) and β-CTX (β = 0.09, 95% CI: 0.06–0.12, p < 0.001). Patients in the highest ALI tertile showed 15%–30% higher BTMs compared with those in the lowest tertile (all p < 0.01). Spline models revealed non-linear relationships with inflection points at ALI ≈ 2.15 for P1NP and 2.47 for β-CTX. No significant associations were observed below these cutoffs, whereas above them, the ALI was positively correlated with both markers. Findings were consistent across subgroups.ConclusionThe ALI is positively and non-linearly associated with bone turnover in OPF patients. A low ALI indicates suppressed remodeling, whereas higher ALI values correspond to increased turnover and potentially greater healing capacity. Incorporating systemic health indices such as ALI may represent a diagnostic advance beyond BMD, improving fracture risk stratification and individualized management. Prospective studies should assess its prognostic utility.